Strategic Cost Analysis - Ong, Audra (Business Expert Press, 2012)
Ebook from IG Library ; Increasing business competition is compelling managers not only to develop realistic and achievable strategies but also to analyze goals in financial terms and to evaluate performance. Managers will need to know the key methods and techniques of strategic cost analysis no matter which sectors they are in - be it manufacturing, service, or the nonprofit sector. The interaction of the organization's activities, the influences of the external world, and the responsibilities of managers need to be captured in financial terms to enable managers to plan, control, and make decisions.